2018
DOI: 10.11604/pamj.2018.30.218.11718
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical survey of herbs used in the management of diabetes mellitus in Southern Katanga Area/DR Congo

Abstract: IntroductionDiabetes is becoming a public health burden for sub-Saharan countries due to its prevalence which is growing rapidly. Traditional medicine is more and more used to treat diabetes in RD Congo as well as in other African countries. This study was undertaken in order to list plants used in the management of diabetes by traditional healers in four agglomerations of southern area of Katanga in the Democratic Republic of Congo.MethodsForty-nine traditional healers were randomly met and interviewed about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
27
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 17 publications
14
27
4
Order By: Relevance
“…The leaves were used more frequently than the other plant part in the preparation of remedies. And is in line with several studies reported in Congo [14,60,61], and elsewhere in Africa [9,62,63], Asia [64,65], or Europe [66]. It is supposed that leaves are easier to collect [45] and could contain more easily extractable phytochemicals, crude drugs, and many other mixtures which may be proven as valuable in phytotherapy [64].…”
Section: Discussionsupporting
confidence: 87%
“…The leaves were used more frequently than the other plant part in the preparation of remedies. And is in line with several studies reported in Congo [14,60,61], and elsewhere in Africa [9,62,63], Asia [64,65], or Europe [66]. It is supposed that leaves are easier to collect [45] and could contain more easily extractable phytochemicals, crude drugs, and many other mixtures which may be proven as valuable in phytotherapy [64].…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, E. abyssinica is the most used plant in traditional medicine in this environment. The preponderance of decoction and drink respectively as a mode of preparation and administration route of aphrodisiac recipes observed in this study (Figure 4) are also reported in several ethnobotanical surveys reviewed in Haut-Katanga [19,37,45]. These studies are in contrast with studies carried out in other regions of the continent [43,44].…”
Section: Discussionsupporting
confidence: 62%
“…In several ethnobotanical studies carried out in Lubumbashi [17,19,33,34] as well as in this study (table 1), it is showed that men over 40 years are the most encountered during the survey, and their level of education is very low. On the other hand, in some surveys conducted in North Africa [35,36], women are the majority in the practice of traditional medicine.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The author declares that there are no conflicts of interest regarding the publication of this paper. Congo [96]…”
Section: Conflicts Of Interestmentioning
confidence: 99%